Correlation between Nasolabial Angle and Maxillary Incisors Inclination in 18–25-Year-Old Chhattisgarh Population Using Pre- and Post-Treatment Lateral Cephalograms: A Retrospective Study - Preeti Paryani; Sunil S. Agrawal; Achint Chachada; Megha Jain; Samkit Bothra; Shreya Shrivastava; Heena Sahni (Indian Journal of Dental Research)
Introduction: One of the primary objectives of orthodontic treatment has been the enhancement of facial aesthetics. To obtain the perfect facial profile with aesthetic balance, knowledge of facial anatomy is essential. The diagnosis and treatment planning of orthodontic patients depend greatly on the examination of the soft tissue profile. Since the nasolabial angle is significantly affected by the inclination of the upper incisors, it is a frequently employed soft tissue parameter in orthodontic diagnosis. Aim: The study aimed to find out the correlation between the nasolabial angles with maxillary incisor inclination. Materials and Methods: In this retrospective study, 120 lateral cephalograms of orthodontic patients including males and females were traced. Their nasolabial angle and maxillary incisor inclination were calculated before and after orthodontic treatment. Result: The mean of pre- and post-treatment nasolabial angle was found to be 91.43° ± 14.008 and 97.93° ± 14.194, respectively. The mean of pre- and post-treatment incisor inclination was found to be 32.59° ± 7.290 and 23.98° ± 6.851, respectively. The gender-wise Pearson’s correlation (r) of nasolabial angle with incisor inclination for male and female was found to be -0.464 with a P value of 0.164 and -0.305 with a P value of 0.118, respectively. Overall Pearson’s correlation of nasolabial angle with incisor inclination was found to be -0.040 with a P value of 0.384. Conclusion: There is an insignificant negative correlation between nasolabial angle and incisor inclination in the Chhattisgarh population as well as among the two genders.